A Randomized Controlled Trial Comparing Telemedicine Versus In-Person Office Visits for the Follow-Up of Overactive Bladder. Issue 12 (8th December 2022) - Mossack, Spencer; Inoyatov, Igor; Fonseca, Philip; Du, Chris; Lee, Edwin; Ruan, Heng; Kim, Jason
Abstract : IMPORTANCE: Overactive bladder is a condition that may be ideally suited for the use of telemedicine because initial treatment options are behavioral modification and pharmacotherapy. OBJECTIVE: We sought to evaluate if there was an overall difference in patient follow-up rates between telemedicine and in-person visits. STUDY DESIGN: New patients presenting with overactive bladder from July 2020 to March 2021 were randomized into telemedicine and in-person visits groups. A prospective database was maintained to compare follow-up rates, satisfaction rates, and time commitment. RESULTS: Forty-eight patients were randomized, 23 to the telemedicine group and 25 to the in-person visits group. There was no significant difference in follow-up rates between the telemedicine and in-person follow-up groups at 30 days (39% vs 28%, P = 0.41), 60-days (65% vs 56% P = 0.51) or 90 days (78% vs 60%, P = 0.17). There was no significant difference in satisfaction rates between the 2 groups. There was a significant difference between the average telemedicine visit time and in-person visit time (12.1 ± 6.9 minutes vs 22.8 ± 17.1 minutes; P = 0.02). For in-person visits, the average travel time was 49 minutes (interquartile range, 10–90 minutes) and average miles traveled was 22.1 miles (interquartile range, 10–70 miles). CONCLUSIONS: There was no significant difference in follow-up or satisfaction rates between telemedicine and in-person visits. Telemedicine visits took half the length of time compared with in-person visits. On average, patients in the telemedicine group saved approximately 1 hour per follow-up visit. Telemedicine visits save both the health care provider and patient significant amounts of time without sacrificing patient satisfaction and follow-up rates.